Affordable overnight lodging in high-cost, high-need coastal environments. Issue 8 (3rd August 2022) - Riggs, William; Rugh, Megyn; Al, Stefan; Sethi, Menka
ABSTRACT: Providing access to coastal and marine resources has long been a planning priority in many locations. At the same time, housing affordability and the lack of investment in lower-cost overnight accommodations in environmentally sensitive coastal areas have exasperated efforts to provide equitable access. While agencies have funded projects to help increase the supply of lower-cost overnight accommodations along the coast, including development of campgrounds, hostels and other facilities, the extent of need has not been quantified and other solutions are needed to preserve and increase supply of lower-cost accommodations along the coast. Further, the synergies between potential policies to address access to the coastal environment and those that promote local housing and transportation efficiency have not been investigated. Using the case of the California Coastal Commission/Conservancy, this paper quantifies the need for access studying the distribution of households at 80% of the median income level within 150 miles of the coast and finds that access to coastal lodging is limited. It hypothesises that broader housing, transportation and equity policies need to be brought into the dialogue to help address lower-cost accommodations in parallel with local environmental, housing and transport issues. Lastly, it offers recommendations and new construction opportunities for low-cost accommodation infrastructure in these kinds of environmentally sensitive areas.